THEORETICAL ASPECTS OF INNOVATIVE MANAGEMENT IN THE ERA OF DIGITALIZATION OF ECONOMY: THEORETICAL ASPECTS OF INNOVATIVE MANAGEMENT IN THE ERA OF DIGITALIZATION OF ECONOMY - Xodjamuratova, Gulbahor (Архив научных исследований, 2021)
In the paper have been discussed theoretical aspects of innovative management in the era of digitalization of economy. By the author were proposed ways for successful implementation of inter-firm innovation processes, managers need to organize closer interaction and cooperation with investors.